Effect of oxygen partial pressure on the growth of molybdenum trioxide thin films. (2019) - Dixit, Divya; Madhuri, K.V.
Abstract: Molybdenum Trioxide (MoO3 ) has high-stability, memory effect, response time and life time. Therefore it has started taking a very useful role in modern day advancements of electronics, electrochemical and optoelectronic devices. In current investigation, molybdenum trioxide thin film was deposited by thermal deposition method onto Indium Tin Oxide (ITO) Coated glass substrates. Effect of oxygen with precise regulation of pressure on the growth of films is aimed to study. MoO3 films are grown under vacuum of 2 × 10 −5 mbar as well as under pressure of 2 × 10 −4 mbar by introducing Oxygen. During the process, substrate temperature (TS ) is maintained at 150 °C. The structural, morphological, vibrational, optical and electrochromic properties were systematically studied by using the characterization techniques such as XRD, SEM, EDS, FTIR, UV–VIS spectrophotometry and Cyclic-Voltammetry. The transformation of structural phase is clearly observed due to the presence of oxygen at the mentioned pressure. Optical data indicates direct allowed transition and optical band gap rises with presence of oxygen. The coloration efficiency of the films have been discussed.